Group Guidance Problem-Solving Techniques Effectively Improve Student Time Management: Teknik Pemecahan Masalah Dalam Bimbingan Kelompok Efektif Meningkatkan Manajemen Waktu Siswa - Arin Okvitta; Indah Lestari; Adnan Fadkhurosi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Secondary education requires adolescents to independently organize daily activities and assume responsibility for balancing academic and non-academic pursuits. Specific Background At SMAN 1 Mejobo Kudus, eleventh-grade pupils currently face severe difficulties in harmonizing organizational commitments with study routines, resulting in delayed assignments, reduced learning concentration, and physical exhaustion. Knowledge Gap Although individualized counseling exists, the specific application of structured collaborative problem-solving to systematically resolve time management deficits among heavily burdened senior high school pupils remains underexplored. Aims This study evaluates the capacity of problem-solving techniques within collaborative guidance sessions to optimize time management behaviors among heavily burdened eleventh-grade pupils. Results Utilizing a one-group pretest-posttest pre-experimental design with eight participants, the analysis revealed a substantial progression in mean time management scores from 60 to 88. Novelty This research specifically demonstrates how integrating systematic problem identification, alternative solution formulation, and collaborative peer evaluation directly resolves the scheduling conflicts of highly ambitious, multi-tasking adolescents. Implications School counselors must implement structured collaborative guidance to empower adolescents with systematic decision-making tools, ensuring they effectively prioritize academic obligations without sacrificing organizational engagement or personal well-being. Highlights Pre-experimental testing demonstrated a significant progression in mean time management scores from 60 to 88. Collaborative guidance interventions successfully resolved scheduling conflicts for highly ambitious, multi-tasking eleventh-grade pupils. Systematic problem identification and alternative solution formulation effectively mitigated delayed assignments and reduced physical exhaustion. Keywords Time Management; Group Guidance; Problem-Solving Techniques; Student Productivity; School Counseling